The human microbiota: the role of microbial communities in health and disease (2016)
During the last decade, there has been increasing awareness of the massive number of microorganisms, collectively known as the human microbiota, that are associated with humans. This microbiota outnumbers the host cells by approximately a factor of ten and contains a large repertoire of microbial genome-encoded metabolic processes. The diverse human microbiota and its associated metabolic potential can provide the host with novel functions that can influence host health and disease status in ways that still need to be analyzed. The microbiota varies with age, with features that depend on the body site, host lifestyle and health status. The challenge is therefore to identify and characterize these microbial communities and use this information to learn how they function and how they can influence the host in terms of health and well-being. Here we provide an overview of some of the recent studies involving the human microbiota and about how these communities might affect host health and disease. A special emphasis is given to studies related to tuberculosis, a disease that claims over one million lives each year worldwide and still represents a challenge for control in many countries, including Colombia.